Detection of Residual Pesticides in Foods - Romero-González, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Pesticides are used worldwide, and despite the fact that organic farming is increasing, they are still widely applied in different countries with pesticide regulations and monitoring programs. This Special Issue will cover the topic of the presence of pesticide residues in food, paying special attention to the use of modern analytical techniques based on chromatographic techniques coupled to mass spectrometry. Generic extraction methods are needed to allow the detection of pesticides with different physic-chemical properties, as well as different families of contaminants can be extracted simultaneously. Nevertheless, pluriresidue methods are still necessary for "orphan" compounds that cannot be included in multiresidue methods. Thus, in addition to targeted pesticides, the scope of this analysis can be increased and nowadays, metabolites are also detected, evaluating the degradation of pesticide residues in different food matrices.